Tostación de sulfuros por reducción carbotérmica - Orozco Santander, Ivana Marcela (2016)
The carbothermic reduction process is a direct reduction of sulfides. It allows a roasting in which higher concentrations of metals such asmolybdenum are obtained by using both a reducing agent (in this case, carbon C) and a sulfur scavenger, such as CaO so as to prevent airtoxic gases pollution such as SO2. In this paper, we analyze sulfur concentrates rich in copper, iron, and molybdenum that are obtainedthrough rougher flotation and differential floats, which give rise to different laws. The concentrates were subjected to a carbothermicreduction process in which the working parameters were studied. The values of both the capturing agent and the reducing agent wereadjusted to retain higher concentrations of sulfur. Analyzing the results obtained, the temperature was set and we reached the optimalworking time and optimum molar ratio of CaO and C for the greatest recovery of metals such as molybdenum.